The worldwide spread of Aedes albopictus: New insights from mitogenomes - Battaglia, Vincenza; Agostini, Vincenzo; Moroni, Elisabetta; Colombo, Giulia; Lombardo, Gianluca; Rambaldi Migliore, Nicola; Gabrieli, Paolo; Garofalo, Maria; Gagliardi, Stella; Gomulski, Ludvik M.; Ferretti, Luca; Semino, Ornella; et al. (Frontiers in Genetics, 2022)
The tiger mosquito (Aedes albopictus) is one of the most invasive species in the world and a competent vector for numerous arboviruses, thus the study and monitoring of its fast worldwide spread is crucial for global public health. The small extra-nuclear and maternally-inherited mitochondrial DNA represents a key tool for reconstructing phylogenetic and phylogeographic relationships within a species, especially when analyzed at the mitogenome level. Here the mitogenome variation of 76 tiger mosquitoes, 37 of which new and collected from both wild adventive populations and laboratory strains, was investigated. This analysis significantly improved the global mtDNA phylogeny of Ae. albopictus, uncovering new branches and sub-branches within haplogroup A1, the one involved in its recent worldwide spread. Our phylogeographic approach shows that the current distribution of tiger mosquito mitogenome variation has been strongly affected by clonal and sub-clonal founder events, sometimes involving wide geographic areas, even across continents, thus shedding light on the Asian sources of worldwide adventive populations. In particular, different starting points for the two major clades within A1 are suggested, with A1a spreading mainly along temperate areas from Japanese and Chinese sources, and A1b arising and mainly diffusing in tropical areas from a South Asian source.